2022
DOI: 10.1186/s13018-022-03101-9
|View full text |Cite
|
Sign up to set email alerts
|

The preemptive effects of oral pregabalin on perioperative pain management in lower limb orthopedic surgery: a systematic review and meta-analysis

Abstract: Background To systematically review the literature and provide a comprehensive understanding of the preemptive effects of oral pregabalin on perioperative pain management in lower limb orthopedic surgery. Method We searched three electronic databases for randomized controlled trials comparing the results of preoperative pregabalin and placebo in patients undergoing lower limb orthopedic surgery. Data analyses were conducted using RevMan 5.4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…There has been considerable research on pregabalin in reducing pain intensity, morphine consumption, and side effects after surgery [ 17 , 19 , 57 , 58 , 59 , 60 ]. We had similar results with a recent review described by Chang et al [ 61 , 62 ] for pain severity scores postoperatively in breast cancer surgery when pregabalin was administrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been considerable research on pregabalin in reducing pain intensity, morphine consumption, and side effects after surgery [ 17 , 19 , 57 , 58 , 59 , 60 ]. We had similar results with a recent review described by Chang et al [ 61 , 62 ] for pain severity scores postoperatively in breast cancer surgery when pregabalin was administrated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and systematic reviews have reported the effect of pregabalin as a perioperative adjuvant analgesic in reducing postoperative acute pain and adverse effects by reducing the opioid dose and pain scores [ 17 , 18 , 19 ]. However, there is only a small amount of evidence for preemptive pregabalin in patients undergoing cancer-related surgery.…”
Section: Introductionmentioning
confidence: 99%
“…30 The result of this study was consistent with Dong et al study which indicated that preoperative pregabalin administration could decrease the cumulative morphine consumption at 24 hours (95% CI −1.17 to −0.78; p < 0.001) and VAS at rest at 24 hours (95% CI −12.57 to −3.71; p < 0.001) and 48 hours (95% CI −11.65 to −3.02; p < 0.001) following total knee arthroplasty. 32 Furthermore, a meta-analysis by Chen et al 33 supported the use of pregabalin before surgery in patients undergoing orthopedic lower limb surgery. In this study, pregabalin administration was associated with lower opioid consumption 24 hours (95% CI [−52.32, −16.63], p = 0.0002), lower dynamic pain intensity 48 hours (95% CI [−0.88, −0.07], p = 0.02) and lower static pain intensity 2 hours (95% CI [−0.50, −0.02], p = 0.04) after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…30 The result of this study was consistent with Dong et al study which indicated that preoperative pregabalin administration could decrease the cumulative morphine consumption at 24 hours (95% CI À1.17 to À0.78; p < 0.001) and VAS at rest at 24 hours (95% CI À12.57 to À3.71; p < 0.001) and 48 hours (95% CI À11.65 to À3.02; p < 0.001) following total knee arthroplasty. 32 Furthermore, a meta-analysis by Chen et al 33 35 evaluated pain 1 and 3 months after open heart surgery and showed that pain during movement at 3 months postoperatively in patients treated with 150 mg pregabalin preoperatively and 75 mg twice a day postoperatively for 5 days is significantly lower (p < 0.05) than patients who did not receive pregabalin. Finally, Agarwal et al 36 reported that pregabalin had a significant effect on reducing pain after laparoscopic cholecystectomy compared to placebo (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of analgesic effect from gabapentin or pregabalin in the postoperative setting is generally robust, but the effect on top of the basic four (see above) is usually minor and the adverse effects of sedation and dizziness may delay discharge and cause falls after discharge [26,55 ▪ ]. Thus, they should be reserved for individual cases where much pain is expected.…”
Section: Other Measures and Drugsmentioning
confidence: 99%